Natural plant products in treatment of pulmonary arterial hypertension - Lili Xiang; Ying Li; Xu Deng; Djuro Kosanovic; Ralph Theo Schermuly; Xiaohui Li (Pulmonary Circulation, 2018)
Pulmonary arterial hypertension (PAH) is a severe disease characterized by progressive remodeling of distal pulmonary arteries and persistent elevation of pulmonary vascular resistance (PVR), which leads to right ventricular dysfunction, heart failure, and eventually death. Although treatment responsiveness for this disease is improving, it continues to be a life-threatening condition. With the clinical efficacy of natural plant products being fully confirmed by years of practice, more and more recognition and attention have been obtained from the international pharmaceutical industry. Moreover, studies over the past decades have demonstrated that drugs derived from natural plants show unique advantages and broad application prospects in PAH treatment, not to mention the historical application of Chinese traditional medicine in cardiopulmonary diseases. In this review, we focus on summarizing natural plant compounds with therapeutic properties in PAH, according to the extracts, fractions, and pure compounds from plants into categories, hoping it to be helpful for basic research and clinical application.